The macroeconomic production of the real : formalities and power in Burkina Faso, Mauritania and Guadeloupe - (:unkn) unknown (My University, 2013)
This thesis examines the exercise of power and its transformations, based on the observation of concrete operations of macroeconomic management in two African countries, Burkina Faso and Mauritania, and one Caribbean territory, Guadeloupe. Its approach involves a combination of anthropology, the sociology of quantification and the historical sociology of the political.The exercise of power rests on practices of economic management that are caught up in a network of relations. There are those who dangle the prospect of steering the economy in accordance with an instrumental logic; there are those turn formal procedures into tools for legitimizing current regimes; and there are those who turn macroeconomic management into the site of a struggle for access to resources. Macroeconomics has many meanings and lies at the centre of a wide-ranging ‘technocratic compromise’. In all three cases studied, the detailed observation of macroeconomic calculation shows that the technocratic ethos is crucial for an understanding of the exercise of power. Social and political struggles over education and the high cost of living, and debates on the illusory claims of reformism, place the numerical approach at the very heart of social and political relations. On the turbulent political scene in Mauritania, Guadeloupe and Burkina Faso, the objects of economic management are at work, guiding the actions of individuals and provoking protest. Indeed, macroeconomics is not just to be found in the office: it is part of the political repertoire of ordinary people. It is rooted both in the specific history of these societies and in the autonomous logics of technique and procedure.
Keywords: African Research